2017
DOI: 10.1111/cdev.12846
|View full text |Cite
|
Sign up to set email alerts
|

Young Children's Moral Judgments, Justifications, and Emotion Attributions in Peer Relationship Contexts

Abstract: Children (n = 160, 4- to 9-year-olds; M = 6.23 years, SD = 1.46) judged, justified, attributed emotions, and rated intent for hypothetical physical harm, psychological harm, and resource distribution transgressions against close friends, acquaintances, disliked peers, or bullies. Transgressions against bullies were judged more acceptable than against friends and disliked peers and less deserving of punishment than against acquaintances and disliked peers. Transgressions against friends were judged least intend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 67 publications
3
38
0
Order By: Relevance
“…Only when the transgressor displayed guilt with an apology were the 4-year-olds able to draw the same conclusion as the 5-year-olds about the wrongdoer's feelings (Vaish et al, 2011, Study 2). Finally, in the context of peer relationships, research has shown that children aged 4 to 9 years attributed less negative emotion to actors transgressing against bullies than against friends (Smetana & Ball, 2018). Therefore, it seems essential to investigate whether the happy victimizer phenomenon occurs when information on the recipient's moral behaviour is introduced.…”
Section: The Pre S Ent S Tudymentioning
confidence: 99%
See 2 more Smart Citations
“…Only when the transgressor displayed guilt with an apology were the 4-year-olds able to draw the same conclusion as the 5-year-olds about the wrongdoer's feelings (Vaish et al, 2011, Study 2). Finally, in the context of peer relationships, research has shown that children aged 4 to 9 years attributed less negative emotion to actors transgressing against bullies than against friends (Smetana & Ball, 2018). Therefore, it seems essential to investigate whether the happy victimizer phenomenon occurs when information on the recipient's moral behaviour is introduced.…”
Section: The Pre S Ent S Tudymentioning
confidence: 99%
“…This evidence suggests that infants and young children can evaluate acts not solely based on their value but also by considering the value of the recipient's previous actions. According to the social-cognitive domain theory (Smetana, Jambon, & Ball, 2014;Smetana & Ball, 2018), children in their sociomoral judgements consider not only the act but also the current context and the recipient's characteristics (Helwig & Principe, 1999;Slomkowski & Killen, 1992). Therefore, children may form sociomoral judgements from different perspectives embedded in different social domains (e.g., moral norms, conventional norms, and social norms).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, according to RRT, moral judgments should be understood as a manifestation of different social relationship motives (Rai & Fiske, 2011). We know that infants (Hamlin & Wynn, 2011; Hamlin et al, 2007) and preschoolers (Bocian & Myslinska Szarek, 2020; Li & Tomasello, 2018; McAuliffe et al, 2015; Smetana & Ball, 2018; Smetana et al, 2014) do not have a simple aversion to individuals who harm third parties, but rather consider whether harmful actions were justified, which suggests that they are capable of making complex social judgments. For example, a recent study had demonstrated that 4‐year‐old children judged harmful behavior as less bad when the behavior was directed at the antisocial recipient than at the prosocial recipient.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, starting at around four years, children take peer relationships, particularly friendship, into account when making third-party moral judgments about harm (e.g. Smetana & Ball, 2018), and 4-to 6-year-olds judge partiality towards friends positively when equal distribution is not an option (Paulus, Christner, & Wörle, 2020). Do such attitudes translate to behavior?…”
Section: Future Directionsmentioning
confidence: 99%